The IL-27 component EBI-3 and its receptor subunit IL-27Rα are essential for the cytoprotective action of humanin on male germ cells†. Issue 3 (16th December 2020) - Jia, Yue; Swerdloff, Ronald S; Lue, YanHe; Dai-Ju, Jenny; Surampudi, Prasanth; Cohen, Pinchas; Wang, Christina
Abstract: Humanin (HN) is a mitochondrial-derived peptide that protects many cells/tissues from damage. We previously demonstrated that HN reduces stress-induced male germ cell apoptosis in rodents. HN action in neuronal cells is mediated through its binding to a trimeric cell membrane receptor composed of glycoprotein 130 (gp130), IL-27 receptor subunit (IL-27R, also known as WSX-1/TCCR), and ciliary neurotrophic factor receptor subunit (CNTFR). The mechanisms of HN action in testis remain unclear. We demonstrated in ex-vivo seminiferous tubules culture that HN prevented heat-induced germ cell apoptosis was blocked by specific anti-IL-27R, anti-gp130, and anti-EBI-3, but not by anti-CNTFR antibodies significantly. The cytoprotective action of HN was studied by using groups of il-27r −/− or ebi-3 −/− mice administered the following treatment: (1) vehicle; (2) a single intraperitoneal (IP) injection of HN peptide; (3) testicular hyperthermia; and (4) testicular hyperthermia plus HN. We demonstrated that HN inhibited heat-induced germ cell apoptosis in wildtype but not in il-27r −/− or ebi-3 −/− mice. HN restored heat-suppressed STAT3 phosphorylation in wildtype but not il-27r −/− or ebi-3 −/− mice. Dot blot analyses showed the direct interaction of HN with IL-27R or EBI-3 peptide. Immunofluorescence staining showed the co-localization of IL-27R with HN and gp130 in Leydig cells and germ cells. We conclude that the anti-apoptotic effects of HN in mouse testes are mediated through interaction with EBI-3, IL-27R, and activation of gp130, whereas the role of CNTFR needs further studies. This suggests a multicomponent tissue-specific receptor for HN in the testis and links HN action with the IL-12/IL-27 family of cytokines. Abstract : The cytoprotective effects of HN in mouse testes are mediated via binding with EBI-3, IL-27R, and activation of gp130. This suggests there is a multicomponent tissue-specific HN receptor in the testis and links HN with the IL-12/IL-27 family of cytokines. Graphical abstract: Model of humanin (HN) interaction with EBI-3, IL-27Rα, and gp130 in male germ cells at baseline and after heat induced stress. Under nonstressed condition (left part), free EBI-3 may bind with p28 to form cytokine IL-27, while IL-27Rα and gp130 may combine with each other to form the IL-27 receptor. CNTFRα may bind gp130 and IL-27Rα to form the HN membrane receptor in neuronal cells. After heat stress in the testis, exogenous HN binds with EBI-3 and interacts with gp130 plus IL-27Rα to activate the downstream Jak/STAT3 pathway. Activated STAT3 suppresses heat-induced male germ cell apoptosis. In our study, the role of CNTFRα cannot be concluded definitely. Our data suggest a different multicomponent and tissue-specific receptor for HN in the testis and linking HN action with the IL-12/IL-27 family of cytokines.